Implementasi Strategi Pembelajaran pada Mata Pelajaran PKN di MI Darul Madani - Abdulgani Jamora Nasution; Lusi Safitri; Desi Rismayani Sinaga; Hamidah Sal’Aty (EduInovasi: Journal of Basic Educational Studies, 2023)
This research is motivated by the efforts of researchers to describe the implementation of PPKN learning strategies at MI Darul Madani. Learning strategy is one component of education that is very influential on the success of teachers in achieving educational goals. The use of one type of strategy tends to produce monotonous teaching and learning activities for students, the learning process will feel stiff and students are less enthusiastic about learning. The teacher has implemented the Inquiry Learning learning strategy, but this strategy is still considered lacking and very boring for students. The purpose of this research was carried out at MI Darul Madani to find out the implementation of PPKN learning strategies and innovative learning strategies suggested by teachers and school principals. This type of research uses qualitative research methods to determine how to find, collect, process and analyze the research data. The conclusion from the results of PPKN learning strategy research, with the innovation of inquiry learning learning strategies students become more active in learning. It is hoped that this research will become information material and input for teaching and learning activities in schools, especially at MI Darul Madani, especially in encouraging students to always increase their interest in learning to achieve more adequately. Keywords: Learning Strategies, PKN Lessons, and Inquiry Learning